2013
DOI: 10.21273/hortsci.48.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Leafy Greens in High Tunnel Winter Production in the Northwest United States

Abstract: Season extension structures like high tunnels make it possible to produce coldtolerant crops during winter months for both a longer cropping season and a winter market season. The effects of location and planting date on the fresh yield of several cultivars of Asian greens (Brassica rapa L.), lettuce (Lactuca sativa L.), and spinach (Spinacia oleracea L.) were examined at Moscow, ID/Pullman, WA, and Vancouver, WA, a cold temperate climate and a mild marine climate, respectively. In Winter 2005-06, 20 cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 12 publications
4
26
0
Order By: Relevance
“…However, this includes times when outside ambient temperature reached 80°F and inside temperature rose to 100°F or above, for example. Temperature advantage of only 3.4 to 10.3°F was reported in a similar test at two locations in Washington State (Borrelli et al, 2013). Soil temperature inside and undercover averaged 7.4 to 9.5°F warmer than outside soil temperature.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…However, this includes times when outside ambient temperature reached 80°F and inside temperature rose to 100°F or above, for example. Temperature advantage of only 3.4 to 10.3°F was reported in a similar test at two locations in Washington State (Borrelli et al, 2013). Soil temperature inside and undercover averaged 7.4 to 9.5°F warmer than outside soil temperature.…”
Section: Resultssupporting
confidence: 56%
“…Soil temperature inside and undercover averaged 7.4 to 9.5°F warmer than outside soil temperature. Borrelli et al (2013) reported a soil temperature advantage of 2.5 to 5.5°F. More careful attention to venting high tunnels on hot days may reduce heat stress in plants and prolong the harvest season, increase yields, or both.…”
Section: Resultsmentioning
confidence: 99%
“…High tunnels are frequently utilized in local vegetable production throughout the United States (Carey et al., ) and have been adopted by many local vegetable growers in the Central United States (Kansas City Food Hub Working Group, ). This growing system has been successfully used for protection from the weather elements, (Lang, ), increasing yield (Lamont, ; Waterer, ), increasing product quality (Lamont, ; Rogers & Wszelaki ), season extension (Borelli et al., ; Galinato & Miles, ; Gude et al., ) and reducing crop disease (Hanson, Marks, & Isaacs, ; Lang, ; Rogers & Wszelaki ) of fresh fruits and vegetables. Spinach, Spinacia oleracea , is a cold season crop frequently grown in high tunnels in the U.S. Great Plains Area (Knewtson, Carey, & Kirkham, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous surveys of commercial growers have shown that high tunnels may be beneficial for the production of winter greens worldwide by protecting crops from inclement weather and through season extension (Lamont, 2009). The use of high tunnels in other states with similar climates to that of northern New Mexico have been successful in growing blackberry, kale, and spinach (Borrelli et al, 2013;Lamont, 2009;Lamont et al, 2003;Yao et al, 2018). In addition, kale, spinach, and blackberry are already being grown and sold in local farmers' markets in northern New Mexico.…”
mentioning
confidence: 99%